‘Intimately Associated for Many Years’: George A. K. Bells and Willem A. Visser’t Hoofts common life-work in the service of the Church Universal - Besier, Gerhard (Kirchliche Zeitgeschichte, 2008)
This article discusses the significance of the relationship of George Bell and Willem Visser't Hooft in the context of the early history of the ecumenical movement and the political crises of the period 1933-1958. Based on their lengthy correspondence, it shows how the two men collaborated in steering the movement through the difficulties of the German Church Struggle, the entanglements of the world war and the controversies of the Cold War. It argues that the gifts and qualities of Bell, the bishop, and Visser't Hooft, the ecumenical statesman, often complemented each other, and that this proved one of the decisive, and defining, alliances of international church life in the middle years of the twentieth century.